Geochemical characterisation of the Late Quaternary widespread Japanese tephrostratigraphic markers and correlations to the Lake Suigetsu sedimentary archive (SG06 core) - Tomlinson, Emma; Albert, Paul G.; Smith, Victoria C.; Suzuki, Takehiko; McLean, Danielle; Miyabuchi, Yasuo; Kitaba, Ikuko; Mark, Darren F.; Moriwaki, Hiroshi; Nakagawa, Takeshi (My University, 2019)
Large Magnitude (6–8) Late Quaternary Japanese volcanic eruptions are responsible for widespread ash (tephra) dispersals providing key isochrons suitable for the synchronisation and dating of palaeoclimate archives across East Asia, the NW Pacific and beyond. The transfer of geochronological information using these eruption deposits demands robust tephra correlations underpinned by detailed and precise volcanic glass geochemical data. Presented here is a major (electron microprobe; EMP) and trace element (Laser ablation inductively coupled plasma mass spectrometry; LA-ICP-MS) characterisation of near-source deposits from a series of large magnitude Japanese eruptions spanning approximately the last 150 ka. These data offer new insights into diagnostic compositional variations of the investigated volcanic sources spanning the Japanese islands. Whilst in the case of the highly productive Aso caldera (Kyushu), we are able to explore compositional variations through successive large magnitude eruptions (50–135 ka). These near-source volcanic glass data are used to validate and refine the visible tephrostratigraphy of the intensely dated Lake Suigetsu sedimentary record (SG06 core), Honshu Island, whilst also illustrating key tephrostratigraphic tie points to other East Asian palaeoclimate records (e.g. Lake Biwa). The identification of widespread Japanese tephrostratigraphic markers in the SG06 sediment record enables us to place chronological constraints on these ash dispersals, and consequently explosive volcanism at source volcanoes situated along the Kyushu Arc, including Kikai, Ata and Aso calderas. The proximal Aso-4 Ignimbrite (Magnitude 7.7) deposit is dated here by 40Ar/39Ar at 86.4 ± 1.1 ka (2σ), and provides a chronological anchor (SG06-4963) for the older sediments of the Lake Suigetsu record. Finally, trace element glass data verify visible ash fall layers derived from other compositionally distinct source regions of Japanese volcanism, including activity along the northern Izu-Bonin arc and North East Japan Arcs. These findings underline the Lake Suigetsu record as central node in the Japanese tephrostratigraphic framework.
PUBLISHED
Keywords: Japanese tephrostratigraphic markers; Lake Suigetsu (SG06 core); Tephrostratigraphy; Volcanic glass chemistry; LA-ICP-MS; Trace elements; Volcanic eruptions; Earth Stratigraphy, Sedimentary Processes